2009
DOI: 10.1097/cnd.0b013e3181a23c86
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Aerobic Capacity After an Exercise Program in Sporadic Inclusion Body Myositis

Abstract: An aerobic exercise program can be safely tolerated by patients with sporadic IBM and can improve aerobic capacity and muscle strength when combined with resistance training. These findings indicate that aerobic and functional muscle strengthening exercise should be considered in the management of patients with IBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 28 publications
0
74
0
4
Order By: Relevance
“…Indirectly, it may suggest that physical activity could be achievable and efficient in sIBM patients. Actually, a recent study showed that an aerobic exercise program could improve muscle strength in such patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, it may suggest that physical activity could be achievable and efficient in sIBM patients. Actually, a recent study showed that an aerobic exercise program could improve muscle strength in such patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally supporting its distinction from PM/DM is the fact that IBM exhibits little response to immunosuppressive therapy [8•, 13-17]. Although there is some modest evidence of the benefit of exercise, IBM is an inexorably progressive disease [7,18,19]. The majority of patients require some type of assistive device for ambulation within 10 years of symptom onset, and many patients eventually require a wheelchair for mobility.…”
Section: Inclusion Body Myositismentioning
confidence: 97%
“…It has been shown in small short-term trials that individualised exercise programs can lead to improvement or maintenance of muscle strength and aerobic capacity, as well as improved quality of life (Johnson et al, 2007, Johnson et al, 2009). However, further investigation is needed to determine the most effective exercise protocols and to establish guidelines for their use in IBM patients.…”
Section: Treatmentmentioning
confidence: 99%